Meconopsis horridula Hook. f. & Thomson extract and its alkaloid oleracein E exert cardioprotective effects against acute myocardial ischaemic injury in mice. (10th August 2020) - Zhao, Feng; Bai, Ruifeng; Li, Junjun; Feng, Xiao; Jiao, Shungang; Wuken, Shana; Ge, Fuxing; Zhang, Qian; Zhou, Xiaochun; Tu, Pengfei; Chai, Xingyun
Abstract: Meconopsis horridula Hook. f. & Thomson (MH) is a traditional Tibetan medicine used to promote blood circulation, remove bruises, remove stasis and relieve chest pain which benefit to cardiovascular diseases. Oleracein E (OE), a major tetrahydroisoquinoline alkaloid, can be isolated from MH ethanol extract. The antioxidant and anti-apoptotic effects of OE have been reported by previous pharmacological research. The objective of this article was to investigate the cardioprotective effects of MH extract and OE in an ICR mouse of acute myocardial ischaemic injury. A left anterior descending (LAD) artery ligation mouse model of AMI was established. In vivo, cardiac function after MH and OE treatment was determined through measurement of EF, FS, LVEDd, and LVEDs by echocardiography. The levels of SOD, MDA, CK-MB and LDH in serum were also detected. A TUNEL assay was used to verify apoptosis. Changes in collagen deposition and inflammatory cell infiltration in ischemic myocardial tissue were observed by histopathological examination. In vitro, H9c2 cells were pre-treated with OE for 6 h, and then cultured in serum-free medium with H2 O2 for 2 h. CCK8 assay measured cell viability, and flow cytometry determined apoptosis levels and ROS content. The mechanism was explored by western blotting. These results showed that MH and OE significantly affected acute myocardial ischaemia by improving cardiac function and that OE downregulated the expression of related proteins in the MAPK signalling pathway. These findings provide substantial evidence of MH may applicate in clinic, and indicate that such medicines have potential value for the treatment of ischaemia-induced heart disease. Graphical abstract: Image 1